Opredelenie vedušcich volevych kacestv u vysokokvalificirovannych legkoatletov s narušeniem zrenija v zavisimosti ot sorevnovatel'noj distancii - Krutko, V. B.; Kravets-Abdullina, A. V.; Shvets, R. R. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
Results of researches on determination of the leading strong-willed qualities at athletes of high classification with visual impairment are presented in article. The study revealed correlations between indicators of assessment of will qualities of highly qualified athletes with visual impairment and results of passing the competitive distance. The results obtained make it possible to improve the quality of the management of the training process in order to achieve and maintain the level of physical fitness of highly qualified athletes with visual impairments.